Effect of an injectable trace mineral supplement on the immune response of dairy calves. (June 2020) - Bates, Andrew; Wells, Matt; Laven, Richard; Ferriman, Line; Heiser, Axel; Fitzpatrick, Clare
Abstract: On a spring calving, pastoral dairy farm, the first 40 heifer calves born after calving mid-point (50% of the herd calved) were blood sampled within 24 h. Thirty were selected, using stratified randomisation to form two equal groups (treatment and control) with the same distribution of serum total protein, copper, selenium, zinc, and manganese concentrations, age and breed. From the remaining 10 calves, five were randomly selected into a sentinel group to assess field exposure to Salmonella spp . All calves received two injections of a killed vaccine containing Salmonella spp. antigens at 2 and 6 weeks of age. Concurrently, the treatment group were injected with 1 mL/50 kg trace mineral supplement (TMS) containing 40 mg zinc, 10 mg manganese, 5 mg selenium, 15 mg copper per mL. Sentinel animals received no injections. All animals were bled from 2 to 9 weeks for assay of immune function. At three and four weeks, white blood cells from TMS calves had an increased percentage of cells phagocytosing (effect size = 9.36 and 4.35) and increased number of bacteria ingested per cell (effect size = 0.93 and 1.52). No differences were detected in gamma interferon response (effect size <0.15) or Salmonella sp. antibody titres (effect size <0.20). Highlights: Infectious diseases are a major threat to new born calves with 5-11% of dairy calves dying before weaning. Previous studies show lower perinatal sickness and death in calves injected at birth with a trace mineral supplement. We show TMS at birth increased the percentage of white blood cells phagocytosing and bacteria ingested per cell.